PtCl2 mediated peripheral transformation of carbatriphyrin(3.1.1) into a meso-fused β–β′ dimer and its monomer analogue. Issue 84 (23rd September 2020) - Murugavel, M.; Adinarayana, B.; Das, Mainak; Peruncheralathan, S.; Palepu, Narasinga Rao; Srinivasan, A.
Abstract : meso -Fused β–β′ carbatriphyrin(3.1.1) dimer and its monomer analogue were achieved by a metal assisted strategy. Abstract : An unprecedented formation of a meso -fused β–β′ carbaporphyrin dimer and its monomer with a keto group was described. These analogues were synthesized from carbatriphyrin(3.1.1.) by a metal assisted strategy using PtCl2 salt in a single step without any prefunctionalized precursors. Upon dimerization, the monomeric ligand with a dianionic core is transformed into a dimeric structure with unique trianionic cores.